Genetic Differentiation in the African Malaria Vector, Anopheles gambiae s.s., and the Problem of Taxonomic Status - Gabriele Gentile; Alessandra della Torre; B. T. A. Maegga; Jeffrey R. Powell; Adalgisa Caccone (2002)
Abstract Of the seven recognized species of the Anopheles gambiae complex, A. gambiae s.s. is the most widespread and most important vector of malaria. It is becoming clear that, in parts of West Africa, this nominal species is not a single panmictic unit. We found that the internal transcribed spacer (ITS) of the X-linked rDNA has two distinct sequences with three fixed nucleotide differences; we detected no heterozygotes at these three sites, even in areas of sympatry of the two ITS types. The intergenic spacer (IGS) of this region also displays two distinct sequences that are in almost complete linkage disequilibrium with the distinct ITS alleles. We have designated these two types as S/type I and M/type II. These rDNA types correspond at least partly to the previously recognized chromosomal forms. Here we expand the geographic range of sampling to 251 individuals from 38 populations. Outside of West Africa, a single rDNA type, S/type I, corresponds to the Savanna chromosomal form. In West Africa, both types are often found in a single local sample. To understand if these findings might be due to unusual behavior of the rDNA region, we sequenced the same region for 46 A. arabiensis, a sympatric sibling species. No such distinct discontinuity was observed for this species. Autosomal inversions in one chromosome arm (2R), an insecticide resistance gene on 2L, and this single X-linked region indicate at least two genetically differentiated subpopulations of A. gambiae. Yet, rather extensive studies of other regions of the genome have failed to reveal genetic discontinuity. Evidently, incomplete genetic isolation exists within this single nominal species.